2022
DOI: 10.35335/midwifery.v10i4.696
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related Of Anemia In Adolescence Girl

Abstract: Anemia during adolescence has a negative effect on growth, cognitive abilities, performance abilities and has a serious impact throughout the reproductive years. The study aims to determine the factors associated with the incidence of anemia in adolescent girls. This type of research method is a cross-sectional study. The sample in this study were female students of class XI and XII at SMAS PGRI 2 Banjarmasin who met the inclusion criteria totaling 75 people. Sampling technique with Total Sampling. The researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…Based on the results of the Chi square test described in table 4, a p-value of 0.045 was obtained (p-value <0.05), so it was concluded that there was a significant relationship between MUAC size and the incidence of anemia in female adolescent in Dawungsari Village, Cilawu Health Center Working Area Garut in 2023. The results of this study support the results of the study Ina et al (2018); Sari et al (2022);and Vaira et al (2022). The Odds Ratio (OR) value was 2.447, which means that female adolescent with the MUAC size category have less chance of experiencing anemia by 2.447 times higher than girls with the normal category of MUAC size.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Based on the results of the Chi square test described in table 4, a p-value of 0.045 was obtained (p-value <0.05), so it was concluded that there was a significant relationship between MUAC size and the incidence of anemia in female adolescent in Dawungsari Village, Cilawu Health Center Working Area Garut in 2023. The results of this study support the results of the study Ina et al (2018); Sari et al (2022);and Vaira et al (2022). The Odds Ratio (OR) value was 2.447, which means that female adolescent with the MUAC size category have less chance of experiencing anemia by 2.447 times higher than girls with the normal category of MUAC size.…”
Section: Discussionsupporting
confidence: 89%
“…The absence of a relationship between MUAC and the incidence of anemia is also supported by research by Utami et al (2021);and Windari et al (2018); performed on pregnant women. The opposite result was shown by the research of Ina et al (2018); Sari et al (2022);and Vaira et al (2022); who got the result that there is a relationship between MUAC and the incidence of anemia. In addition, research (Ahankari et al, 2020) shows that there is a relationship between MUAC and hemoglobin levels.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…The purpose of this improper diet is to reduce food portions and limit food consumption without paying attention to the intake of nutrients needed by the body. As the future generation of the nation, the problem of anemia in young women needs to receive serious attention because if it continues to be ignored, it can make teenagers easily tired, weak, fatigued, limp, and lethargic (5L), reduce fitness, and can reduce academic grades due to decreased concentration and achievement learning and disruption of work productivity (Vaira et al, 2022) Some data shows that cases of anemia among young women in Indonesia are still high. According to Riskesdas 2013, the prevalence of adolescent girls experiencing anemia was 37.1%, and the prevalence increased in 2018 to 48.9%, with the proportion of anemia in the age groups 15-24 years and 25-34 years (Zhang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in Indonesia, the prevalence of Anaemia in adolescent girls was found to be 32% 4,5 . A study of high school girls in South Kalimantan, Indonesia, found 29.3% had Anaemia 6 . In a survey conducted in West Java, Indonesia, 41% of the adolescent girls were anaemic 7 .…”
Section: Introductionmentioning
confidence: 99%